Synthesis, characterization, thermal behavior, and DFT calculation of solid 1,4-bis(3-carboxy-3-oxo-prop-1-enyl) benzene of some trivalent lanthanides - Ferraretto, Ana Clara [UNESP]; Nunes, Ronaldo Spezia [UNESP]; Luiz, Jose Marques [UNESP]; Caires, Flavio Junior [UNESP]; Treu-Filho, Oswaldo [UNESP]; Ionashiro, Massao [UNESP] (Springer, 2014)
Solid-state Ln(2)L(3)center dot nH(2)O compounds, where Ln represents trivalent lanthanides (from Eu to Lu and Y, except Dy) and L is 1,4-bis(3-carboxy-3-oxo-prop-1-enyl) benzene, have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry, X-ray powder diffractometry, infrared spectroscopy, and complexometry were used to characterize and to study the thermal behavior of these compounds. The dehydration of the compounds occurred until at 445 K (Y), at 440 K (Tb), and at 489 K (Eu, Gd, Ho, Er, Tm, Yb, and Lu). After dehydration, the DTA curves showed two other thermal events that are associated with the thermal decomposition of the compounds with formation of the respective oxides. The results also provided information about the composition, dehydration, crystallinity, and thermal decomposition of these compounds. Furthermore, the theoretical and experimental spectroscopic data suggest the possible modes of coordination of the ligand with the metals.
Keywords: 1,4-bis(3-carboxy-3-oxo-prop-1-enyl) benzene; Trivalent lanthanides; Thermal behavior; DFT